The Role of Perceived Entrepreneurial Feasibility in The Influence of Altruism on College Students' Social Entrepreneurial Intention - Prayoga, Bintang Eko Dwi; Susilaningsih, Susilaningsih; Indriayu, Mintasih (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to analyze the role of perceived entrepreneurial feasibility as a mediator between altruism and college studentsâ€™ social entrepreneurial intention (SEI). This research used a quantitative approach within a cross-sectional design. The sample for this study comprised 309 people (from a total population of 1.364 people) using proportionate stratified random sampling from several undergraduate programs in the Universitas Sebelas Maret grades of 2020th and 2021st. This research instrument used a questionnaire that was adopted and developed based on previous research instruments. Statistical analysis techniques were used to conduct descriptive, correlational, and mediation tests with path analysis using IBM SPSS Statistics 25 software. The results indicated that altruism has a significant direct effect on perceived entrepreneurial feasibility (Î² = 0,484; p < 0,001) and SEI (Î²= 0,310; p < 0,001). Furthermore, the results also revealed that perceived entrepreneurial feasibility plays a vital role with a strong direct effect on SEI (Î² = 0,523; p = 0,001) while also acting as a partial mediator between altruistic and SEI of college students.Â Therefore, university policymakers and educators need to integrate the values of altruism into the curriculum to increase perceived entrepreneurial feasibility and SEI among college students.